Blue highways revisited - Ailor, Edgar I., III (University of Missouri Press, 2012)
"In 1978, William Least Heat-Moon made a 14,000-mile journey on the back roads of America, visiting 38 states along the way. In 1982, the popular Blue Highways, which chronicled his adventures, was published. Three decades later, Edgar Ailor III and his son, Edgar IV, retraced and photographed Heat-Moon's route, culminating in Blue Highways Revisited, released for publication on the thirtieth anniversary of Blue Highways. A foreword by Heat-Moon notes, 'The photographs, often with amazing accuracy, capture my verbal images and the spirit of the book. Taking the journey again through these pictures, I have been intrigued and even somewhat reassured that America is changing not quite so fast as we often believe. The photographs, happily, reveal a recognizable continuity -- but for how much longer who can say -- and I'm glad the Ailors have recorded so many places and people from Blue Highways while they are yet with us.' Through illustrative photography and text, Ailor and his son capture once more the local color and beauty of the back roads, cafes, taverns, and people of Heat-Moon's original trek"--Book dust-jacket.